2001
DOI: 10.1128/jvi.75.14.6273-6278.2001
|View full text |Cite
|
Sign up to set email alerts
|

Common Antiviral Cytotoxic T-Lymphocyte Epitope for Diverse Arenaviruses

Abstract: Members of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
18
0
2
Order By: Relevance
“…10,14,15,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Studies of convalescent sera from patients with Lassa Fever or human HLA transgenic mice identified a number of epitope targets within the NP, GP1, GP2 and GS proteins. 11,12,16,19,[57][58][59][60][61][62][63] Recent work in a guinea pig model utilizing the GP1 and GP2 proteins in a DNA vaccine resulted in adequate protection from challenge virus. [13][14][15][16]20 Our review of Lassa vaccine development efforts did not show that the Lassa L protein has ever been used as part of the antigens in a subunit vaccine, although the L protein was shown to be protective in animal studies of other arenavirus like lymphocytic choriomeningitis virus.…”
Section: Discussionmentioning
confidence: 99%
“…10,14,15,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Studies of convalescent sera from patients with Lassa Fever or human HLA transgenic mice identified a number of epitope targets within the NP, GP1, GP2 and GS proteins. 11,12,16,19,[57][58][59][60][61][62][63] Recent work in a guinea pig model utilizing the GP1 and GP2 proteins in a DNA vaccine resulted in adequate protection from challenge virus. [13][14][15][16]20 Our review of Lassa vaccine development efforts did not show that the Lassa L protein has ever been used as part of the antigens in a subunit vaccine, although the L protein was shown to be protective in animal studies of other arenavirus like lymphocytic choriomeningitis virus.…”
Section: Discussionmentioning
confidence: 99%
“…The LCMV NP 118-126 epitope shares 78% homology with LASV and MOPV NP and constituted more than 97% of the total bulk CTL produced in BALB mice. The 118-126 aa peptides derived from the NP of LCMV, LASV and MOPV bound at high affinity to L d [155].…”
Section: Lasv Np Expressed In Vaccinia Virusmentioning
confidence: 99%
“…ter Meulen et al have already identified LASVspecific CD4 ϩ T-cell epitopes that are conserved with other arenavirus family members (40). Similarly, in murine models, cross-reactive CD8 ϩ T-cell epitopes have been identified among several arenaviruses, including LASV, LCMV, and Pichinde virus (24,28) While our approach to epitope identification in this study was tailored specifically for LASV, it represents a model system that could be applied to any virus (or other intracellular pathogen). The minimum requirements needed to utilize this approach are (i) existing sequence data for the pathogen in question, (ii) access to the genome (DNA or RNA) of the pathogen for the purpose of generating rVV vectors, (iii) HLA transgenic mice, and (iv) access to BSL-2 facilities for in vitro and in vivo studies.…”
Section: Fig 7 Functional Avidity Of Cd8mentioning
confidence: 99%